ANALISIS TENTANG PELAKSANAAN KUDA LUMPING YANG DIMAINKAN OLEH ANAK-ANAK DI KEPENGHULUAN MUKTI JAYA KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Darsono, Darsono; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the implementation of kuda lumping phenomenon in which there are children. Children are involved in the appearance of kuda lumping to maintain the existence and preservation of kuda lumping, kuda lumping loaded with violence and magic usually played by adults, but in this case children who are mentally and physically not ready for things related to the element of violence and the magic. Kuda lumping is also always held at night until late at night. This phenomenon raises the perception or response of the community of Village Mukti Jaya. So the authors take a study entitled "Analysis of Implementation of kuda lumping Played By children In Village Mukti Jaya District Rimba Melintang Regency Of Rokan Hilir". This study aims to determine the implementation of kuda lumping played by children and the public perception of children dancers in kuda lumping. Respondent in this research is 102 people by using technique of Purposive Sampling. Data collection techniques are done through observation, questionnaires, interviews and documentation. The research method used is descriptive quantitative. This method is done by processing data whose data is presented through percentage calculation and given the answer. Based on the results of the study, the implementation of kuda lumping played by children are mostly in the appropriate category (50% -100%), with a percentage gain of 64.06%. And the public perception of children dancers in kuda lumping is in good category (50% -100%), with a percentage gain of 74%.Keywords: Kuda lumping